2019
DOI: 10.2337/dc18-1760
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on the Safety and Efficacy of Exenatide Therapy for the Inpatient Management of General Medicine and Surgery Patients With Type 2 Diabetes

Abstract: OBJECTIVEThis multicenter, open-label, randomized trial examined the safety and efficacy of exenatide alone or in combination with basal insulin in non-critically ill patients with type 2 diabetes (T2D). RESEARCH DESIGN AND METHODSA total of 150 patients with blood glucose (BG) between 140 and 400 mg/dL, treated at home with diet, oral agents, or insulin at a total daily dose <0.5 units/kg, were randomized to exenatide alone (5 mg twice daily), exenatide plus basal insulin, or a basal-bolus insulin regimen. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 38 publications
1
37
0
7
Order By: Relevance
“…It was also reported that the abundance of Firmicutes was positively associated with adiposity (Zhang et al, 2020). Nevertheless, other studies have found the negative or no correlation, suggesting that the association between obesity and gut microbiota were likely to be influenced by several factors (Fayrman et al, 2019). Thus, the relationship between the ratio of microbiota and obesity have so far been inconclusive.…”
Section: A-cmentioning
confidence: 99%
“…It was also reported that the abundance of Firmicutes was positively associated with adiposity (Zhang et al, 2020). Nevertheless, other studies have found the negative or no correlation, suggesting that the association between obesity and gut microbiota were likely to be influenced by several factors (Fayrman et al, 2019). Thus, the relationship between the ratio of microbiota and obesity have so far been inconclusive.…”
Section: A-cmentioning
confidence: 99%
“…The safety and efficacy of noninsulin glucose-lowering therapies in the hospital setting is an area of active research (57,58). Several recent randomized trials have demonstrated the potential effectiveness of glucagon-like peptide 1 receptor agonists and dipeptidyl peptidase 4 inhibitors in specific groups of hospitalized patients (59)(60)(61)(62). However, an FDA bulletin states that providers should consider discontinuing saxagliptin and alogliptin in people who develop heart failure (63).…”
Section: Noninsulin Therapiesmentioning
confidence: 99%
“…Hypoglycemia was de ned as blood glucose < 3.9 mmol/L, with or without symptom. Hyperglycemia was de ned as blood glucose > 13.3 mmol/L (Fayfman, et al, 2019;Pasquel, et al, 2017). Aspiration was de ned as gastric content appeared in the mouth and entered the trachea or lungs.…”
Section: Data Collection and Outcome Assessmentmentioning
confidence: 99%